Heavy Metals in Moss and Bark From Urban Area of Florence: A New Cleaness Procedure for Removing Superficial Particulate Matter - Ducceschi, L.; Legittimo, P. Cellini; Bonzi, L. Morassi (Chemistry and Ecology, 1999)
Abstract Hypnum cupressiforme epiphytic moss and tree bark (elm and holm oak) samples have been collected in three sites of the city of Florence in the period 1995?1998. Lead, zinc, copper, and cadmium were determined by differential pulse anodic stripping voltammetry (DPASV) in about 200 samples collected at different heights above ground. A new clean-up procedure by nitrogen jet has been followed and its efficiency has been also verified by electron microscopy (SEM and ESEM techniques). Lead median contents in moss and bark samples fall within the ranges of 0.052?0.86 and 0.20?1.30 ?moles g?1 (dry weight), resulting values for moss and bark are proportional to the vehicular traffic density. the increasing use of lead-free gasoline has not been followed by a decrease of lead moss concentration.
doi: 10.1080/02757549908037642doi: 10.1080/02757549908037642The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: Bark; biomonitoring; environmental scanning electron microscopy (ESEM); Heavy metals; Moss